2011
DOI: 10.1136/bmjopen-2011-000127
|View full text |Cite|
|
Sign up to set email alerts
|

Sensor recorded changes in rates of hand washing with soap in response to the media reports of the H1N1 pandemic in Britain

Abstract: ObjectivesTo examine how the frequency of information regarding a real disease threat influences hand washing with soap.Design and settingThe authors installed wireless devices in highway service station lavatories in England to record the proportion of individuals washing hands with soap from May 2009 to January 2010.ParticipantsParticipants were users of men's and women's toilets. Combined there was an average of 6800 participant entrances into the lavatories daily.Primary outcome measureThe primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(41 reference statements)
0
26
0
4
Order By: Relevance
“…Newly emerging sensor technologies are likely to provide more accurate measures (Fleischman et al . ; Ford et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Newly emerging sensor technologies are likely to provide more accurate measures (Fleischman et al . ; Ford et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions developed through theorydriven approaches have been able to demonstrate substantial shifts in observed hygiene behaviour in non-outbreak settings [23][24][25][26][27], but we know little about whether theorydriven approaches are feasible or effective in emergency settings, or how similar or different the determinants of behaviour change are. For example, communicating health risks during infectious disease outbreaks may be more effective than in non-outbreak settings [28,29], but may only have short term effects [30]. Using motives like disgust, shame or nurture (the desire to do what is best for your child) might be just as relevant in emergencies, but there may also be additional ethical considerations of using such motivators with vulnerable communities [31,32].…”
Section: Changing Hygiene Behavioursmentioning
confidence: 99%
“…Another study used sensors in public toilets to measure hand washing behaviors and found that hand washing rates inclined at times when the volume of H1N1 media reporting was highest (Fleischman et al. ). It follows then that the cultivation of fear in populations is required to mobilize them and that news media can be the way to produce such a response.…”
Section: Introductionmentioning
confidence: 99%